2008
DOI: 10.1128/jvi.00872-08
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of Cytoplasmic Poly(A)-Binding Protein upon Rotavirus Infection Involves the Interaction of NSP3 with eIF4G and RoXaN

Abstract: Rotavirus nonstructural protein NSP3 interacts specifically with the 3 end of viral mRNAs, with the eukaryotic translation initiation factor eIF4G, and with RoXaN, a cellular protein of yet-unknown function. By evicting cytoplasmic poly(A) binding protein (PABP-C1) from translation initiation complexes, NSP3 shuts off the translation of cellular polyadenylated mRNAs. We show here that PABP-C1 evicted from eIF4G by NSP3 accumulates in the nucleus of rotavirus-infected cells. Through modeling of the NSP3-RoXaN c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
105
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 55 publications
3
105
0
6
Order By: Relevance
“…Recently, Ilkow et al (24) demonstrated that PABP is sequestered by the capsid protein of rubella virus, which results in a block in translation. By contrast, the NSP3 protein of rotavirus indirectly influences the nuclear accumulation of PABP (20,35). Whether BUNV N induces nuclear targeting of PABP is currently unclear, as is the importance of the interaction of these proteins for the BUNV life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ilkow et al (24) demonstrated that PABP is sequestered by the capsid protein of rubella virus, which results in a block in translation. By contrast, the NSP3 protein of rotavirus indirectly influences the nuclear accumulation of PABP (20,35). Whether BUNV N induces nuclear targeting of PABP is currently unclear, as is the importance of the interaction of these proteins for the BUNV life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, during rotavirus infection, PABP is evicted from eIF4G by NSP3 (9) and relocalizes to the cell nucleus (16). These observations led to the idea that the shutdown of cellular protein synthesis is due to the eviction of PABP and, hence, to the displacement of cellular polyadenylated mRNAs from eIF4G.…”
mentioning
confidence: 94%
“…Additionally, PABP1 partially relocalizes to the nucleus during HSV-1 infection (40,41). Rotavirus protein NSP3A functionally replaces and evicts PABP1 from the eIF4F complex and leads to nuclear relocalization of PABP1 (42,43). Kaposi's sarcoma-associated herpesvirus SOX protein expression leads to PABP1 relocalization to the nucleus (44).…”
mentioning
confidence: 99%